Comparative study of safety and efficacy of Fentanyl and Midazolam combination with Ketamine and Midazolam combination for procedural sedation in pediatric patients - Agarwal, Akansha; Chanchlani, Roshan; Pahelajani, Jyoti (International Journal of Medical Research and Review, 2015)
Introduction: Study was planned to compare the safety and efficacy of Fentanyl and Midazolam combination with Ketamine and Midazolam combination for “procedural sedation” in pediatric patients. Methodology: Sixty ASA1and 2 pediatric patients satisfying inclusion criteria were included in the study. These patients were enrolled by convenience sampling. They were randomized to receive ketamine or midazolam/fentanyl. Both the groups were comparable with respect to age, sex and body weight and proposed procedures. Hemodynamic and respiratory changes occurring during sedation, surgical procedure and during recovery, after administration of the test drug were studied. Measures used for efficacy of drug, that is quantification of distress, pain, anxiety, sedation and complications were also evaluated. Results: On Comparison of age, gender, weight at different time intervals of cases between both groups were comparable with respect to age and weight of patients. On comparison of Pulse Rate at different time intervals of cases between K/M and F/M groups. The mean value of Pulse Rate in K/M and F/M groups is statistically significant (p<0.05) only at 5 and 10 minutes after sedation. Comparison of Mean Duration of Procedure and Recovery of cases between K/M and F/M groups shows statistically non-significant difference (p<0.05) in duration of procedures, and statistically significant difference (p<0.05) in duration of recovery. Comparison of complication rate of cases between K/M and F/M groups is statistically non-significant (p<0.05). Conclusion: We concluded that both the drugs were safe to use in pediatric patients in the doses used intravenous. Ketamine / Midazolam regimen is more effective than the intravenous Fentanyl / Midazolam regimen for relief of pain and anxiety in children, resulting in lesser distress scores.